The Effect of Islamic Corporate Governance and Maqashid Sharia Index on Firm value with Islamic Social Reporting as a Moderating Variable - Zaenal Alim Adiwijaya; Edy Suprianto; Dedi Rusdi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The need for organizational governance is currently a major issue in Islamic banks. This is important to increase the profitability of Islamic banks and investor confidence. The research aims to examine the effect of Islamic Corporate Governance and the Maqashid Sharia Index on Firm Value with Islamic social responsibility as a Moderating Variable. The population of this research used all Islamic commercial banks registered with Bank Indonesia (BI) and the Financial Services Authority (OJK). The study is explanatory research by selecting samples with the criteria: First, Islamic banks have presented their financial statements from the 2018-2020 period and could be accessed on the official websites of each Islamic bank or other official websites. Second, Islamic commercial banks have published the GCG Statement which can be accessed on the official website of Islamic banks. Based on the analysis results, it can be concluded that Islamic Corporate Governance and the Maqashid Sharia Index have a positive and insignificant effect on firm value. However, these results proved that ISR was able to moderate the relationship between Islamic Corporate Governance and the Maqashid Sharia Index with firm value.